Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1093/jn/132.7.2065
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Elderly People Is Influenced by Vitamin E Status

Abstract: The aim of this study was to examine associations between vitamin E status and cognitive performance in elderly people. The study subjects were a group of 34 men and 86 women, aged 65-91 y, who were free of significant cognitive impairment. Dietary intake was monitored using a "weighed food record" for 5 consecutive days including a Sunday. Serum levels of alpha-tocopherol and cholesterol were determined by HPLC and colorimetric methods, respectively. The cognitive capacity of subjects was tested using the Pfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 18 publications
2
33
0
3
Order By: Relevance
“…Some group B vitamins, such as folic acid, cyanocobalamine and pyridoxine are essential for correct brain function; inadequate status in these nutrients has been associated with loss of cognitive function (Ortega et al, 1996;Selhub et al, 2000). In addition, certain dietary antioxidants, such as b-carotene and vitamins C and E potentially protect against cognitive decline by limiting the negative effects of free radicals (Launer & Kalmijn, 1998;Berr et al, 2000;Ortega et al, 2002). In contrast, high consumption of total fats, saturated fatty acids (SFA) and cholesterol has been associated with increased cholesterolaemia, an increased risk of cardiovascular disease, and impaired intellectual function (Hernando, 2000;Ortega et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some group B vitamins, such as folic acid, cyanocobalamine and pyridoxine are essential for correct brain function; inadequate status in these nutrients has been associated with loss of cognitive function (Ortega et al, 1996;Selhub et al, 2000). In addition, certain dietary antioxidants, such as b-carotene and vitamins C and E potentially protect against cognitive decline by limiting the negative effects of free radicals (Launer & Kalmijn, 1998;Berr et al, 2000;Ortega et al, 2002). In contrast, high consumption of total fats, saturated fatty acids (SFA) and cholesterol has been associated with increased cholesterolaemia, an increased risk of cardiovascular disease, and impaired intellectual function (Hernando, 2000;Ortega et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical deficiencies can affect health and functional capacity both in the short and long term (Lachance, 1998;Ortega, 1999;Ortega et al, 2002;Puska, 2002;Lewis et al, 2003). Improving the nutritional status of the population is a priority both at the collective and individual level (Ortega, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is fully accepted that an adequate nutritional status is important for maintaining and restoring health and for improving mental and functional capacity (Ortega et al, 2002;Puska, 2002;Lewis et al, 2003). The theoretical benefits of achieving recommended intakes (RI) include delaying the onset of chronic diseases and enhanced quality of life (with a concomitant increase in functional capacity, productive longevity and reduced healthcare costs) (Lachance, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly population studied by Ortega et al, dietary intake of vitamin C, -carotene and vitamin E were associated with a better cognitive function (Ortega et al, 2002). Perrig et al (Perrig et al, 1997) showed that higher plasma ascorbic acid and -carotene concentrations were associated with better memory performance in older people, both cross-sectionally and longitudinally over a 22 year period.…”
Section: Studiesmentioning
confidence: 96%